The Flexible Alternative Consumer Financing in Malaysia: Credit Cards - Rasiah, Devinaga (Journal of Social and Development Sciences, 2013)
This study examines the changes occurring in the consumption behavior of the Malaysian consumers towards the use of credit cards as a source of consumer finance. Use of credit cards as payment had considerably multiplied in Malaysia ever since 1990s. Supported by the conceptual framework, five independent variables were employed. This was evaluated with respect to one dependent variable in this study. The dependent variable was the credit card. The questionnaire was tested using 160 questionnaires, using validity test, linear correlation, descriptive statistics and multiple regressions to test the results. The results indicated that there was a relationship between credit card debts, attitude, income, understanding/knowledge, potential impact of credit card utilization among bank customers. The study can be used by banks to be aware of the increased usage of credit cards which can give rise to increase in consumer finance in the future.